Structure and breakdown property relationship of polyethylene nanocomposites containing laboratory-synthesized alumina, magnesia and magnesium aluminate nanofillers. (September 2018) - Samad, A.; Lau, K.Y.; Khan, I.A.; Khoja, A.H.; Jaffar, M.M.; Tahir, M.
Abstract: The emergence of polymer nanocomposites has led to a new field of study in advanced dielectrics. Commonly, a few weight percent of single-metal oxide nanofillers has been added to polymers, and promising dielectric property changes have been found. Nevertheless, contradictory results have also been reported, where the use of single-metal oxide nanofillers has also resulted in degraded breakdown performances. Recently, experimental studies on ceramics showed that multi-element oxide ceramics could have a compact structure with entirely different chemical, mechanical and electrical properties from single-metal oxide ceramics. This approach is, however, less pursued from the perspective of dielectrics. In the current work, the structure and breakdown properties of polyethylene nanocomposites containing laboratory-synthesized single-metal oxide nanofillers, i.e., alumina (Al2 O3 ) and magnesia (MgO), and multi-element oxide nanofiller, i.e., magnesium aluminate (MgAl2 O4 ) nanofiller were compared. The results showed that the use of MgO resulted in higher breakdown strength of the nanocomposites than the use of Al2 O3 . Significantly, the use of MgAl2 O4 resulted in much higher breakdown strength of the nanocomposites than MgO and Al2 O3, and that the breakdown values could be comparable or even higher than the unfilled polyethylene under DC and AC applied fields. Possible mechanisms governing these property changes are discussed. Highlights: Al2 O3, MgO and MgAl2 O4 nanofillers were synthesized and characterized. Properties of single-metal oxide and multi-element oxide nanofillers were compared. Nanocomposites with MgAl2 O4 had higher breakdown strength than Al2 O3 and MgO. Breakdown strength of MgAl2 O4 nanocomposites was comparable to unfilled counterpart. Possible mechanisms governing the property changes are discussed.